Local Revenue Management and Financial Performance of Local Governments: A Case Study of Mbale District - Wamandu Luke (Uganda Christian University, 2024)
The study established the relationship between local revenue management and financial performance in local governments with specific reference to Mbale District Local Government. Based on this, three specific objectives were formulated and these are; to examine the relationship between local revenue planning and financial performance Mbale district local government; to assess the relationship between local revenue collection and financial performance Mbale district local government and to determine the relationship of local revenue control and financial performance in Mbale district local government. This study adopted a case study research design using triangulation approach in which both qualitative and quantitative techniques of data collection were used. The study found out that there is a significant positive relationship between local revenue planning, local revenue collection, local revenue control and financial performance in Mbale local government. It was concluded that an effective and efficient local revenue management is very critical for enhancing financial performance in local governments. Consequently, the study recommends that all the key stakeholders be involved in local revenue planning, collection and the effectuation of a meaningful internal local revenue control mechanisms that will guarantee proper allocation of resources the long financial performance in Mbale Local Government among other local governments since they share common mistakes